Nutraceutical, cosmetic, health products derived from olive - D'Andria R.; Di Salle A.; Petillo O.; Sorrentino G.; Peluso G. (Present and future of the Mediterranean olive sector, 2013)
It is widely recognized that the Mediterranean diet is associated with a reduced rates of chronic disease (i.e. cardiovascular disease, atherosclerosis, some types of cancers, and Alzheimer’s disease), and a higher life expectancy. These health benefits have been partially attributed to the dietary consumption of olive oil by populations residing in the Mediterranean region, and more specifically the phenolic compounds naturally present in olive fruit and oil. In vitro and in vivo studies have demonstrated that these phenolic compounds have potentially beneficial biological effects resulting from their antimicrobial, antioxidant and anti-inflammatory activities. This paper summarizes the modes of action by which olive phenolic compounds beneficially influence health parameters.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)